Mathematical modeling of gap junction coupling and electrical activity in human β-cells. (25th September 2015) - Loppini, Alessandro; Braun, Matthias; Filippi, Simonetta; Morten Gram Pedersen,
Abstract: Coordinated insulin secretion is controlled by electrical coupling of pancreatic β -cells due to connexin-36 gap junctions. Gap junction coupling not only synchronizes the heterogeneous β -cell population, but can also modify the electrical behavior of the cells. These phenomena have been widely studied with mathematical models based on data from mouse β -cells. However, it is now known that human β -cell electrophysiology shows important differences to its rodent counterpart, and although human pancreatic islets express connexin-36 and show evidence of β -cell coupling, these aspects have been little investigated in human β -cells. Here we investigate theoretically, the gap junction coupling strength required for synchronizing electrical activity in a small cluster of cells simulated with a recent mathematical model of human β -cell electrophysiology. We find a lower limit for the coupling strength of approximately 20 pS (i.e., normalized to cell size, ∼2 pS pF −1 ) below which spiking electrical activity is asynchronous. To confront this theoretical lower bound with data, we use our model to estimate from an experimental patch clamp recording that the coupling strength is approximately 100–200 pS (10–20 pS pF −1 ), similar to previous estimates in mouse β -cells. We then investigate the role of gap junction coupling in synchronizing and modifying other forms of electrical activity in human β -cell clusters. We find that electrical coupling can prolong the period of rapid bursting electrical activity, and synchronize metabolically driven slow bursting, in particular when the metabolic oscillators are in phase. Our results show that realistic coupling conductances are sufficient to promote synchrony in small clusters of human β -cells as observed experimentally, and provide motivation for further detailed studies of electrical coupling in human pancreatic islets.